Visual merchandising strategies of selected apparel retail stores - Susi, Ma. Genevieve Abbie
Visual merchandising is one of the essential tools in product and store promotion. Strategies based on the visual merchandising goals and objectives of the company are planned and formulated in order to maximize the function of store displays (Swanson and Everette, 2000). Visual merchandising strategies of apparel stores differ because of different brand/store image and different target markets. These are evident in the way they present merchandise in the two visual merchandising environments, which are the windows and interiors. The study aimed to determine the visual merchandising strategies applied on store windows and interiors by the selected apparel retail stores. It specifically aimed to determine how they arrange merchandise in the selling area and how they utilized the display elements such as the merchandise, props, and color in their window and interior spot displays. Data collection relied primarily on interviews with the visual-merchandisers of the selected apparel retail stores. Four apparel retail stores agreed to participate in the study when informed about confidentiality of information. The interview guide questionnaire was divided into tow parts. The first half is about the visual merchandising goals and objectives of the apparel retail store. It also included questions on the visual merchandising staff and visual merchandising policies of the selected apparel retail stores. The second half was composed of questions about the presentation and arrangement of merchandise in the selling area. It also included questions on how display elements such as the merchandise props, color were manipulated in windows and interior spot displays of the selected apparel retail stores. Written materials like books, journal, and articles from the net served as secondary sources. Along with the information given by the visual merchandisers, actual pictures of store displays were included to better illustrate the strategies. Results were presented in table forms. Results of the study provided insights on how the participating apparel retail stores execute store displays and how they arrange merchandise to fit their stores image and to appeal to their target market. The strategies showed the different approaches in visual merchandising practiced by the selected apparel retail stores in order o accomplish their main objective, which is to generate sales by presenting their merchandise in the best way possible. The window and in-store spot displays of the participating apparel retail stores were coordinated in terms of the merchandise being displayed on the mannequins. Mannequin presentation varied depending on the displayed clothing line. Mannequin poses varied depending on the look the store wants to achieve. Photo walls and tarpaulins were used as window backgrounds. Merchandise was presented either by outfit presentation or product class presentation. Apparel retail store A presented its products using both outfit and product class presentation. Apparel retail store B and C presented merchandise mainly by groups or coordinated items. Apparel retail store D used 50% outfit and 50% product class presentation type. Merchandise was presented either front facing or side facing displayed on wall modules, and merchandise racks. Garments were arranged or hung on racks and hang bars according to certain order for each of the participating retail stores. Clothes and accessories were also displayed on tables with mannequin torsos clothed with the same mannequin merchandise on the table. Visual merchandising strategies based on results of the study were slightly different for each of the participating retail stores. The visual presentations of the stores reflect their target market and store brand/image. Mannequins were not considered as props but were treated as primary element of the display. Windows and spot displays were mostly simple and practical; the stores' focus was more on the arrangement of their merchandise in the selling area. A similar study with more apparel retail store respondents would be effective in providing a general picture of the visual merchandising strategies of local retail stores. Consumer purchasing behavior in relation to visual merchandising would also be an interesting topic for study as well as the evaluation of the visual merchandising strategies through personal feedbacks of regular mall shoppers.